PLATELET LUMIAGGREGATION TESTING: REFERENCE INTERVALS AND THE EFFECT OF ACETYLSALICYLIC ACID IN HEALTHY ADULTS - Trampuš Bakija, Alenka; Jazbec, Janez; Faganel Kotnik, Barbara (Journal of Medical Biochemistry, 2020)
Background: Light transmission aggregometry with lumiaggregometry are methods commonly recommended as a first-line test in platelet dysfunction diagnostic work-up. They are poorly standardized and usually performed in specialized laboratories. For proper interpretation, each laboratory should establish its own diagnostic approach in order to recognize abnormal aggregation patterns. The aim of this study was to measure plasma lumiaggregometry with basic agonists to establish the analyzer-reagent reference intervals (RI) for adults and to test the method response to aspirin.Methods: The Chrono-Log Model 700 lumiaggregometer using Chrono-Par and Chrono-lume reagents (Chrono-Log Corp., Havertown, PA, USA) was used to measure the maximal aggregation and adenosine triphosphate release using adenosine diphosphate (2 mmol/L), collagen (2 mg/mL), arachidonic acid (1 mmol/L), epinephrine (5.5 mmol/L) and ristocetin (1.25 mg/mL), and thrombin (1 U/mL). The effect of aspirin on platelet aggregation and granule release was inspected.Results: RIs derived from 40 healthy adults were calculated using the non-parametric approach. Wider intervals and low lower limits were determined for weak agonist as well as absence or impaired aggregation in up to one of 7 healthy controls. The response of platelets to aspirin shows response comparable to previously reported study.Conclusions: Locally established RI in our study enable us to investigate platelet function in patients with a high probability of bleeding disorders. Values are agonist and equipment specific. The variability of the method can be reduced by considering standardized preanalytical and analytical variables. Pathological results must be interpreted in the context of other hemostasis test results and clinical findings.
Keywords: blood platelets; platelet aggregation; platelet function test; reference values